Pusa Gynoecious Cucumber Hybrid-18 - Munshi, A D; Behera, T K; Sureja, Amish K; Tomar, B S; Singh, J; Dey, S S (Indian Horticulture, 2021)
The cucumber (Cucumis sativus L.), known as Khira in Hindi is a very popular and important vegetable grown in hills and plains of India. It is used as salad, pickle and also as cooked vegetable. Apart from being used as salad, it is also used for pickling and rayata preparation. Due to good taste and low energy content, they are regarded as refreshing condiment. In north Indian plains, generally two crops are taken in a year viz. spring-summer and kharif season crops. The consumer preference in India is long cylindrical type, medium thick indigenous (desi) hybrid of cucumber with earliness and high yielding ability. Keeping in view these facts, a gynoecious cucumber hybrid Pusa Gynoecious Cucumber Hybrid-18 was developed by Division of Vegetable Science IARI, New Delhi and recommended by AICRP (vegetable crops) for cultivation in Zone I [Humid Western Himalayan Region i.e. Jammu & Kashmir (J&K), Himachal Pradesh and Uttarakhand] during spring- summer and kharif season and subsequently notified by central sub -committee on crop standards, notification and release of varieties of horticultural crops during the year 2021.